COVID-19 vaccination in patients with breast cancer and gynecological malignancies: A German perspective. (December 2021) - Forster, Marie; Wuerstlein, Rachel; Koenig, Alexander; Amann, Niklas; Beyer, Susanne; Kaltofen, Till; Degenhardt, Tom; Burges, Alexander; Trillsch, Fabian; Mahner, Sven; Harbeck, Nadia; Chelariu-Raicu, Anca
Abstract: Introduction: The side effects of systemic cancer therapy and the lack of clinical data on safety and efficacy of COVID-19 vaccination in cancer patients cause uncertainty among the patients about whether to get vaccinated or not. Here, we evaluated attitude towards and effects of COVID-19 vaccination in patients with breast and gynecological cancer undergoing systemic cancer therapy. Methods: Since March 15th, 2021, cancer patients who received one of the approved COVID-19 vaccines were routinely interviewed about immediate and late side effects. Clinical parameters such as current therapy, time interval between therapy administration and vaccination, and changes in the therapy schedule due to vaccination were documented. The collected data were analyzed de-identified as a part of routine quality assurance. Results: By July 27th, 2021, 218 patients (74.3% breast cancer patients) had received one of two COVID-19 vaccine doses, and 112 patients had received both doses: 77.5% received Conmirnaty (BioNTech/Pfizer), 16.1% Vaxzevria (Astra Zeneca) and 5.9% COVID-19 Vaccine Moderna. The COVID-19 vaccines had an acceptable safety profile with self-limiting local and systemic adverse events, which rarely lasted >48 h post vaccination. Symptoms occurred predominantly after the second dose of the vaccine and less frequently in older patients >55 years. No vaccine-related serious adverse events were reported, and only limited effects of vaccination on the therapy schedule were observed. Conclusions: Breast and gynecologic cancer patients tolerate the COVID-19 vaccination while undergoing systemic cancer therapy without any additional side effects beyond those reported in the general population. Highlights: COVID-19 vaccine was safe in 218 breast and gynecological cancer patients. Cancer patients appear to be rather skeptical about COVID-19 vaccination. vaccine-related adverse events were self-limiting and mostly of short duration. COVID-19 vaccines had limited effects on the schedule of anti-cancer therapies.